Workplace relational injustice and authoritarian treatment as risk factors for sexual harassment at a large Swedish university: results from a cross-sectional study - Pilgaard, Frida; Agardh, Anette ; 0000-0002-1879-7244; Östergren, Per-Olof; Palmieri, Jack ; 0000-0002-7430-3157; Asamoah, Benedict Oppong (BMC Public Health, 2025)
Background Workplace sexual harassment remains a persistent issue in Sweden. Research about organisational antecedents has been criticised for being limited in scope, possibly overlooking contextual factors relevant for the occurrence of sexual harassment. This study examined two factors capturing aspects of organisational climate, perceived relational justice and authoritarian treatment, and their association to workplace sexual harassment in a Swedish university setting. Methods Cross-sectional data from a 2019 survey targeting all Lund University employees was used. Validated instruments were employed to measure relational justice, authoritarian treatment and sexual harassment. Bivariate and multivariable regression analyses, stratified by gender, were conducted using Poisson regression models and additive interaction analysis performed, calculating synergy index (SI) and relative excess risk due to interaction (RERI). Results The adjusted prevalence ratio (PR) of sexual harassment was statistically significantly higher among participants who perceived low relational justice (RJ), with a PR of 1.8 (95% CI 1.3–2.6) among women and PR 2.2 (95% CI 1.01–4.6) among men. A similar pattern was seen among participants who perceived high authoritarian treatment (AT), with a PR of 2.0 (95% CI 1.4–2.9) among women and PR 3.4 (95% CI 1.7–6.9) among men. Interaction analyses indicated that women and participants with a foreign background perceiving low relational justice or high authoritarian treatment have a higher probability of sexual harassment compared to men and participants with a Swedish background with the same perceptions. Furthermore, that participants with low or non-academic positions perceiving low relational justice have a lower probability of sexual harassment compared to those with high academic positions. Conclusion Our findings suggest that superiors’ unjust or authoritarian treatment of employees might be contextual factors contributing to workplace sexual harassment, disproportionally affecting women, employees with a foreign background or high academic positions. To ensure evidence-based interventions, researchers should incorporate organisational risk factors in the design and evaluation of workplace interventions aimed at reducing sexual harassing behaviours.